Militância e organização: um estudo sobre o CELLOS-MG - Andressa Carolina do Nascimento Nunes (2022)
CELLOS-MG (Centre for the Fight for Free Sexual Orientation of Minas Gerais) presents itself as an entity that postulates, among its main objectives, the “fight against LGBTphobia and any forms of prejudice due to sexual orientation or gender”, as well as the “awareness of the LGBT population about the defense of their fundamental rights, in addition to the formation of new militants”. Located in the city of Belo Horizonte, the entity acts as the organized movement of civil society representing LGBT+ in its local, state and national forums. The focus of this research turned to CELLOS-MG as a type of organization that emerged from the activisms related to the field of sexuality, because, on the one hand, we consider the production of subjectivities — mainly the Foucauldian strand, which states the effects of power relations and discourses as producers of subjectivities — as part of the political dimension of people's sexuality. On the other hand, we consider the history of theoretical development from the experiences of activists and social movements. Therefore, the central idea of this thesis is to problematize the modes of existence of these subjects, in order to reveal their power relations, the practices that constitute the organizational spaces and the elements of the current hegemonic sexual matrix that constitute these subjects and that are imbricated in the dynamics of space organization that informs the movement. For that, we used the methods of documental research and semi-structured qualitative interview for data collection, while the archeogenalogical enunciative analysis undertaken was developed considering Michel Foucault's writings and theories about the very methods used to conduct his genealogies and archeologies. Among the findings of the analysis, we sought to highlight the organization as a collective subject of morals and politics, highlighting the organization's rules and norms, its internal functioning and its strategic positions in the power-resistance relations in which it is inserted. Likewise, we approach the “Belo Horizonte LGBT Parade” as an event that is subject to interdictions and disputes, at the same time that it represents a space for enunciations and visibility of the bodies of marginalized subjects. Por fim, discutimos os processos de constituição dos membros militantes em suas três dimensões principais: enquanto sujeitos sexuais, políticos e da moral “cellista”.